Penerapan Sistem E-Commerce pada Khalwa Store Berbasis Web - Sri Heneng Prasastono; Widodo Wibisono (Jurnal Manajemen Bisnis Digital Terkini, 2026)
Khalwa store is a clothing store. The e-commerce site is built on a manual system. The current manual system relies solely on sales to customers who visit the store. Furthermore, bookkeeping for sales recapitulation reports is still done manually, resulting in incomplete and incomplete sales reports. Many companies and businesses are now utilizing e-commerce as a support system to enhance effectiveness and efficiency. Khalwa store, a micro-enterprise selling clothing, lacks a support system for its business operations. Therefore, a system that can address this issue is needed to improve store management in terms of service and marketing. The results of this research created a web-based e-commerce design that will improve the existing system to make it more effective and efficient in promotion and marketing. This web-based e-commerce system can significantly impact Khalwa store sales turnover, as customers come not only from the surrounding area but also from outside the area.